Barriers and facilitators of advance care planning practices in multi-disciplinary, multi-facility palliative care for Japan’s aging population: A qualitative analysis - Mariko Tanimoto; Norihiro Okamura; Kaku Sawada; Tomofumi Igarashi; Mitsunori Nishikawa (PLoS ONE, 2025)
Globally, multi-disciplinary advance care planning (ACP) in multi-facility settings for aging communities is essential; however, it does not consistently yield the desired outcomes. Japan’s population is rapidly aging; nonetheless, no studies have examined comprehensive ACP implementation by diverse professionals across various community healthcare facilities. Within the context of an aging community, this study aimed to identify the barriers and facilitators to ACP implementation by multiple professionals in various healthcare facilities. A qualitative research design was employed. The study participants included 22 multidisciplinary members of a community-based palliative care (CBPC) team. Individual semi-structured interviews were conducted between September and October 2019. A total of 19 barriers and 19 facilitators were identified and categorized into seven practice domains: “Understanding patients’ intentions,” “Family support,” “Information sharing using tools,” “Collaboration among multiple professions,” “Cross-facility and cross-departmental cooperation,” “Raising awareness in the community,” and “Efforts by implementation promoters and their departments.” Barriers included “Inability to understand the patient’s intentions,” “Physical and psychological distance between patient and family,” and “Different information needs and sharing methods at each facility,” among others. Facilitators included “Skills for better understanding the true meaning of patients’ intentions,” “Compatibility of daily tasks and ACP by utilizing tools,” “Human connections between professionals in multiple facilities and departments,” and “Engagement with ACP implementation,” among others. The study identified important domains for practical ACP implementation using a community-based palliative care team collaborating across multiple community facilities, as well as the barriers and facilitators. The findings indicate that multi-disciplinary, multi-facility ACP implementation in regions with aging populations requires establishing a regional collaborative network system and a human network. Healthcare professionals must develop practical ACP experience to identify its benefits while enhancing their skills as “advocates.”